2021
DOI: 10.1177/25158414211040898
|View full text |Cite
|
Sign up to set email alerts
|

The effect of amblyopia on clinical outcomes of children with astigmatism

Abstract: Background: Amblyopia is more common in children with high astigmatism, but factors contributing to development of amblyopia and visual outcomes are not fully understood. Objective: To evaluate the effect of amblyopia on the clinical outcomes in children with ⩾1.75 diopter (D) astigmatism. Methods: We reviewed the medical records of children with ⩾1.75 D astigmatism with and without amblyopia (amblyopes group and non-amblyopes group). The mean age, gender, amount and type of ocular deviation, presence of conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
0
1
Order By: Relevance
“…found that amblyopic children with high magnitude of astigmatism have diminished peak amplitudes in the orientation-specific visual evoked potentials in all the meridians tested, rather than in just a single meridian [34]. The relatively small sample size in our study did not permit us to investigate this in detail.…”
Section: Astigmatismcontrasting
confidence: 56%
“…found that amblyopic children with high magnitude of astigmatism have diminished peak amplitudes in the orientation-specific visual evoked potentials in all the meridians tested, rather than in just a single meridian [34]. The relatively small sample size in our study did not permit us to investigate this in detail.…”
Section: Astigmatismcontrasting
confidence: 56%